Training and overtraining: an overview and experimental results in endurance sports - Lehmann, M. J.; Lormes, W.; Opitz-Gress, A.; Steinacker, J. M.; Netzer, N.; Foster, C.; Gastmann, U. (The Journal of Sports Medicine and Physical Fitness, 1997)
Overtraining is defined as "Training/competition to recovery imbalance." It primarily is caused by too little time for regeneration. Additional non-training stress sources, such as social, educational, occupational, nutritional, and travel factors and the monotony of training increase the risk of overtraining. Symptoms of overtraining are persistent performance incompetence, persistent high fatigue rating, altered mood state, increased rate of infections, and suppressed reproductive function. This review considered three studies that evaluated effects on participants.